Extra-Capsular Dissection in Parotid Pleomorphic Adenoma: A Viable Alternative Technique to Superficial Parotidectomy? - Shiraz Shaikh, Zameer Hussain Laghari, Champa Sushel, Aisha Memon, Rehmat Urf Sehrish Shah, Seema Anwar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the effectiveness of extra-capsular dissection in parotid pleomorphic adenoma as compared to superficial parotidectomy. Material and Method: The study took place over the time of a year, from January 2021 to December 2021 at the Department of General Surgery, Liaquat University of Medical and Health Sciences. All patients who presented with parotid pleomorphic adenoma, age more than 12 years of either gender, were included. All the cases were divided into groups based on the type of surgical technique. Patients underwent superficial parotidectomy were kept in group A and those who underwent extra-capsular dissection were kept in group B. During the personal follow-up presentations, all patients received a clinical examination, facial nerve assessment, and personal standardized interviews after surgery. Clinical signs of the facial nerve weakness and Frey's syndrome were recorded. All the data were collected by study proforma and SPSS version 26 was used for the purpose of data analysis. Results: A total of 41 patients were selected and particularly studied by dividing them into two groups. Mean age of superficial parotidectomy group’s patients was 37.43+4.71 years and mean age of the extra-capsular dissection group was 33.22+5.31 years. The average operating time was significantly less in extra-capsular dissection group 43.03+10.7 min (p- 0.001). Estimated average blood loss was also significantly less in the extra-capsular dissection group 36.38+11.47 ml (p-0.001). Males were most common in both groups and the average size of excised glands was also statistically insignificant among both groups (p->0.05). The signs of facial nerve weakness were higher in superficial parotidectomy group 7(30.4%) of 23 cases compared with 2(11.1%) in the extra-capsular dissection group of 18 cases, while statistically insignificant (p-0.138). Frey's syndrome was observed in 2 patients in the superficial parotidectomy group and not found in the extra-capsular dissection group (p-0.200). Conclusion: Extra-capsular parotidectomy was observed to be the feasible, reliable and noninvasive in terms of less operating time, less blood loss, minimal chances of facial nerve weakness and no evidence of Frey's syndrome compared to superficial parotidectomy technique in the treatment of parotid pleomorphic adenoma